Upaya Penerapan Budidaya Ikan Dalam Ember (Budidamber) Di SDN Kauman 1 Kota Blitar - Ananda Nabila Laraswari; Stevi Putri Adolvina Baik; Usamah Abdul Haq; Bagus Indra Kurniawan; Prasmita Dian Wijayati; Dewi Puspa Arum (Jurnal Kabar Masyarakat, 2023)
Limited land availability poses a challenge for urban communities interested in developing fish farming activities. As the years go by, the increasing population leads to a scarcity of land in urban areas, which can hinder the development of fish farming activities by limiting access to natural resources. One solution to overcome land limitations in fish farming is the use of the bucket fish farming method. This method efficiently utilizes limited space and is cost-effective, allowing for fish farming in urban environments, such as at SDN Kauman 1 in Blitar City. This creative innovation involves students and the community in fish farming activities using buckets, with the goals of environmental education, practical learning, and skill development for students. The objective of this community service activity is to provide guidance on understanding and effectively implementing bucket fish farming (Budidamber) in a sustainable manner. The methods used include socialization, preparation, and implementation. It is expected that this journal will contribute positively to supporting local food resilience and environmental conservation at SDN Kauman 1 in Blitar City and its surrounding community.